Effect of 5-aza-2Ëˆ-deoxycytidine on p27Kip1, p21Cip1/Waf1/Sdi1, p57Kip2, and DNA methyltransferase 1 Genes Expression, Cell Growth Inhibition and Apoptosis Induction in Colon Cancer SW 480 and SW 948 Cell Lines: - Kavoosi, Fraidoon; Sanaei, Masumeh; Nasiri, Sedighe (Galen Medical Journal, 2020)
Background: Dysregulation of the cell cycle has been reported in various cancers. Inactivation of the cyclin-dependent kinases inhibitors (CDKIs), CIP/KIP family, such as p21Cip1/Waf1/Sdi1, p27Kip1, and p57Kip2 genes because of hypermethylation has been shown in several cancers. Treatment with DNA demethylating agent 5-aza-2Ëˆ-deoxycytidine (5-Aza-CdR) has been indicated that affect genomic methylation and resulting in silenced genes reactivation in colon cancer. Previously, we evaluated the effect of 5-Aza-CdR on DNA methyltransferase 1 (DNMT1) gene expression in hepatocellular carcinoma (HCC) which encouraged us to design the current study. The present study aimed to evaluate the effect of 5-Aza-CdR on p21Cip1/Waf1/Sdi1, p27Kip1, p57Kip2, and DNAT1 genes expression, cell growth inhibition and apoptosis induction in colon cancer SW 480 and SW 948 cell lines. Materials and Methods: The effect of 5-aza-CdR on the SW 480 and SW 948 cells growth, apoptosis induction and genes expression were assessed by MTT assay, flow cytometry, and real-time quantitative reverse transcription-polymerase chain reaction (qRT-PCR) analysis respectively. Results: 5-aza-CdR inhibited cell growth as time- and dose-dependent manner significantly (P<0.001). The agent reactivated p15INK4, p16INK4, p18INK4, and p19INK4 genes expression and induced apoptosis at a concentration of 5 Î¼M significantly. Besides, 5-aza-CdR had a more significant effect on the SW 480 cell line in comparison to SW 948 cell line. Conclusion: 5-Aza-CdR plays a key role in the up-regulation of p21Cip1/Waf1/Sdi1, p27Kip1, and p57Kip2 and down-regulation of DNMT1 genes resulting in cell growth inhibition and apoptosis induction. [GMJ.2020;9:e1899]